(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: The current study is theoretically grounded in the Technology Acceptance Model (TAM) and Social Influence Theory. It attempts to explain how acts of others influence attitudes and behaviors of individuals in the context of the adoption of cloud computing services. Methodology: The present study used the convenience sampling technique to conduct empirical research. Data collection was performed via an online survey. We used Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the proposed research model. Results: Our findings suggest that a favorable social norm towards cloud computing services produces a positive and statistically significant effect on perceived ease of use, perceived usefulness, and willingness to use cloud computing services. In terms of mediating the role of perceived ease of use and perceived usefulness, findings revealed that perceived ease of use mediates the relationship between social norms and willingness to use cloud computing services. Conclusion: The present study advances our understanding of the role of social influence and individual perceptions of technology (i.e., usefulness and ease of use) in the intention to use technology in the cloud computing context.